Profesionalitas Kinerja Guru dalam Paradigma Birokrasi New Public Service - Dewi Nursilowati; Kibtiyani (Nusantara Innovation Journal, 2024)
Bureaucracy in every country has experienced significant progress. As the complexity of the problems faced by public administrators grows, bureaucratic changes adapt to these conditions. The bureaucratic paradigm, which previously could be manipulated and prioritized the interests of groups rather than society, has now transformed into the NPS or New Public Service bureaucratic paradigm. NPS is a bureaucratic paradigm viewed from the aspect of justice where all citizens have the right to receive the same services. However, the NPS paradigm as the newest bureaucratic management has special requirements where every citizen who wants to get services must be accompanied by finances. The realm of education in Indonesia cannot be separated from bureaucracy related to finance, starting from uniforms; study module books; as well as academic services. This research aims to explain the relationship between teacher professionalism and teacher performance in the NPS bureaucratic system. The research objects in this case are PPPK teachers spread across East Kalimantan. Teacher professionalism in implementing NPS is reviewed in terms of extensive education, competency, work autonomy and code of ethics at work. Professionalism greatly influences the implementation of NPS, demonstrated through the Serve Citizen, not customer aspect; Seek the public interest; Think strategically, act democratically and value people, not just productivity. The respondents in this study were 37 PPPK teachers who took part in training at the East Kalimantan BPSDM institution. The method in this research uses descriptive quantitative. Sampling used a non-probability sampling technique, Quota Sampling type. The implications of professionalism policy in the NPS paradigm were obtained in the medium category with the accumulated variable X getting a value of 59% and variable Y with an accumulated value of 81%. This finding states that teachers who apply the NPS paradigm are not necessarily professionals, while professional teachers have clearly implemented the NPS bureaucracy in their work. Data was obtained by distributing questionnaires on the professionalism scale and NPS scale. The hypothesis test in this study used a simple linear regression test which obtained a value of Tstat > Ttable, namely 5.570 > 2.030, so it can be concluded that Ha is accepted. And the significant influence of professionalism on NPS is 47%. The positive constant value is 7.578 and the professionalism variable value is proven to be positive with an accumulation of 0.661.